2021
DOI: 10.1017/s1041610221000375
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional association between objective cognitive performance and perceived age-related gains and losses in cognition

Abstract: Objectives: Evidence linking subjective concerns about cognition with poorer objective cognitive performance is limited by reliance on unidimensional measures of self-perceptions of aging (SPA). We used the awareness of age-related change (AARC) construct to assess self-perception of both positive and negative age-related changes (AARC gains and losses). We tested whether AARC has greater utility in linking self-perceptions to objective cognition compared to well-established measures of self-perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 59 publications
4
32
0
Order By: Relevance
“…On the other hand, poorer cognition and the subsequent perception of cognitive decline and fear of loss of function may predict symptoms of depression and anxiety (Hill et al, 2016;Kessler et al, 2012;Mol et al, 2008). If this is the case, promoting the acceptance of age-related cognitive changes (Hahn & Lachman, 2015;Huntley et al, 2017;Sabatini et al, 2020Sabatini et al, , 2020aSabatini et al, , 2021, boosting positive effects, decreasing negative effects (Crane et al, 2007), and consultation with health professionals (Hill et al, 2016) may all be potential strategies to reduce SCD and SMD. Alternatively, SCD, SMD, depression and anxiety may all be caused by other factors; for instance, they may both be the consequence of cognitive decline and of neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, poorer cognition and the subsequent perception of cognitive decline and fear of loss of function may predict symptoms of depression and anxiety (Hill et al, 2016;Kessler et al, 2012;Mol et al, 2008). If this is the case, promoting the acceptance of age-related cognitive changes (Hahn & Lachman, 2015;Huntley et al, 2017;Sabatini et al, 2020Sabatini et al, , 2020aSabatini et al, , 2021, boosting positive effects, decreasing negative effects (Crane et al, 2007), and consultation with health professionals (Hill et al, 2016) may all be potential strategies to reduce SCD and SMD. Alternatively, SCD, SMD, depression and anxiety may all be caused by other factors; for instance, they may both be the consequence of cognitive decline and of neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whereas some studies explored whether SCD predicts current cognitive functioning, others explored the predictive role of SCD for future cognitive functioning (Jessen et al, 2014;Jonker et al, 2000;Mendonça et al, 2016;Sabatini et al, 2021). Exploring whether SCD predicts future objective cognitive decline may be the preferred approach, especially with respect to testing the potential use of SCD to identify those individuals at higher risk of cognitive decline.…”
mentioning
confidence: 99%
“…The better physical and mental health, and cognitive functioning in the group experiencing many gains and few losses extends literature reporting the separate associations between more AARC gains and better physical and mental health and between fewer AARC losses and better physical and mental health, and cognitive functioning (Sabatini et al, 2020a;Sabatini et al, 2021a). The class having "many gains and few losses" had better physical and mental health, and cognitive functioning than the class experiencing "moderate gains and few losses," suggesting that the presence of gains may be related to higher levels of physical and mental health, and cognitive functioning.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, higher levels of AARC losses across the ve AARC life domains are correlated with worse cognitive performance (Sabatini et al, 2021a;Zhu and Neupert, 2020). Only one cross-sectional study found that higher levels of AARC gains are related to poorer cognitive performance; however, associations were small to negligible (Sabatini et al, 2021a). As health is more strongly associated with AARC losses than AARC gains (Sabatini et al, 2020a), individuals' current cognitive functioning may be captured by perceived losses, irrespective of the coexistence of perceived gains.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation